Epidemiology of brown rot on two apple cultivars in an organic apple orchard - Holb, I. J.; Gáll, J. (International Journal of Horticultural Science, 2013)
In a two-year-study, the temporal development of brown rot (Monilinia fructigena) on fruits was analysed in an organic apple orchard on an early (Prima) and one late (Idared) maturing cultivars at Debrecen-Józsa in Hungary. Out of five mathematical functions (linear, exponential, three-parameter logistic, Gompertz, Bertalanffy-Mitscherlich), the three-parameter logistic function gave the best fit to brown rot incidence of all cultivars in both years. Disease progress started at the end of June for cv. Prima and at the end of July for cv. Idared, then disease increased continuously from 6-8 weeks up to harvest in all cultivars. Descriptive disease variates derived from the three-parameter logistic function were used to analyse disease progress. These were: Yf, the final disease incidence; Y55, fruit incidence at day 55; Y95, fruit incidence at day 95; b and q, the relative and the absolute rate of disease progress, respectively; T1.5, the time when disease incidence reaches 1.5 %; M, the inflection point and AUDPC, area under disease progress curve. Descriptive disease variates were significantly different (P<0.05) for cv. Prima compared to cv. Idared, except for the relative and absolute rate of disease increase, b and q, respectively. The largest differences among cultivars were in the values of the AUDPC. Disease progress curves and descriptive disease variates were presented and the practical implications of the results were discussed.